Role of Bacteria in chronic Suppurative Otitis Media and Sensitivity pattern in Baqubah Teaching Hospital - Muhammed, Nasser Khalil; Hamood, Hayder Jasim (Diyala Journal of Medicine, 2019)
Background: Otitis media is an inflamation of middle ear, it is either acute or chronic,chronic may be otitis media with effusion(intact tympanic membrane) or may be chronic suppuratve otitis media(there is a perforation in the eardrum)which is aninflamation of middle ear mucosa and mastoid air cells for a period more than 3 months. This inflamation is either a sequely of acute suppurative otitis media (tubotympanic disease)or may be due to a cholesteatoma(atticoantral disease). Objective:To determine type of bacteria that most commonly cause this inflammation and the sensitivity pattern of this bacteria to antibiotics. Patients and Methods: We took 197 patients that we diagnose them clinicaly as cases of chronic suppurative otitis media (with central perforation in the tympanic membrane)(which mean tubotympanic type)and we stopped antibiotic treatment for 3 days(if the patient on this treatment) then we collect samples of pus from the affected ear and then we sent these samples to the lab for bacteriologic study to evaluate the results. Results:Pseudomonas aeruginosa was the most common microorganism involved in our cases of chronic suppurative otitis media followed by Staphylococcusaureussensetivity pattern of Pseudomonas aeruginosa showed thatciprofloxacillin was active against (95%) of isolates followed by amikacin (85%) followed by gentamycin (81%), ceftazidime (80%)and ceftriaxone (50%) Conclusion: The present study reveals that Pseudomonas aeruginosawas the most common pathogen followed by staphylococcus aureusisolated from chronic suppurative otitis media. Ciprofloxacilline was found to be the most suitable antibiotic followed by amikacin and ciftazidime for Pseudomonas aeruginosa. The resistance against Ceftriaxone was found to be high.